Mauritania : Counting on Natural Wealth for a Sustainable Future - Mele, Gianluca (World Bank, Washington, DC, 2014)
A data set of key macro-sustainability indicators, constructed after several fact-finding missions, and World Bank methodologies on estimating wealth accounting are used to study Mauritania's wealth, which is estimated to be between USD50 and USD60 billion. The country's produced wealth represents roughly 12 percent of total wealth, much less than in lower-middle-income countries; by contrast, natural wealth represents approximately 45 percent of the total figure. Renewable resources account for slightly less than two-thirds of natural wealth, with fisheries alone equaling about one-fourth of natural wealth. This is good news for Mauritania, as sound management of these resources may ensure a constant flow of resources in the future and therefore -- with adequate policies -- the achievement of the same or higher levels of welfare for future generations. On the negative side, however, the ratio of net adjusted savings over gross national income is estimated to have been negative since 2006, meaning that the wealth of the country is being depleted. Mauritania has recently joined the ranks of lower-middle-income countries, largely thanks to its considerable natural resources endowment. Over time the mining sector's contribution to gross domestic product has grown significantly and important discoveries continue to be made. The overarching objective of this wealth accounting exercise is thus to support Mauritania to measure its assets better and achieve a more complete picture of the prospects for future income, with a view to better orienting public policies toward sustainable growth and shared prosperity. The paper concludes with several indicative policy recommendations.